2020
DOI: 10.3389/fnins.2020.565815
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Patterns of Pleasurable Musical Chills Revealed by High-Density EEG

Abstract: Music has the capacity to elicit strong positive feelings in humans by activating the brain's reward system. Because group emotional dynamics is a central concern of social neurosciences, the study of emotion in natural/ecological conditions is gaining interest. This study aimed to show that high-density EEG (HD-EEG) is able to reveal patterns of cerebral activities previously identified by fMRI or PET scans when the subject experiences pleasurable musical chills. We used HD-EEG to record participants (11 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 64 publications
6
41
0
1
Order By: Relevance
“…These findings are concordant with past music research, which demonstrated that pleasant music was associated with increased frontal theta power 40 43 . Previous studies even proposed that frontal theta may represent a gating mechanism for the passage of information to the limbic system 41 and showed that the limbic system’s activity directly correlates with theta oscillations in the frontal cortex, particularly in response to emotionally arousing musical stimuli 40 , 42 , 43 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are concordant with past music research, which demonstrated that pleasant music was associated with increased frontal theta power 40 43 . Previous studies even proposed that frontal theta may represent a gating mechanism for the passage of information to the limbic system 41 and showed that the limbic system’s activity directly correlates with theta oscillations in the frontal cortex, particularly in response to emotionally arousing musical stimuli 40 , 42 , 43 .…”
Section: Discussionsupporting
confidence: 92%
“…Our investigation revealed enhanced frontal theta power following shifts from longer musical segments (i.e., 10-s or more) that was not present during transitions from shorter musical segment boundaries and during all transitions within the filtered version of K448 and Wagner’s Lohengrin Prelude to Act I. These findings are concordant with past music research, which demonstrated that pleasant music was associated with increased frontal theta power 40 43 . Previous studies even proposed that frontal theta may represent a gating mechanism for the passage of information to the limbic system 41 and showed that the limbic system’s activity directly correlates with theta oscillations in the frontal cortex, particularly in response to emotionally arousing musical stimuli 40 , 42 , 43 .…”
Section: Discussionsupporting
confidence: 90%
“…We hypothesized that when pairs of participants simultaneously reported similar emotions, the simultaneous activation of similar cerebral structures would produce similar oscillatory patterns, and thus a higher interindividual cerebral coupling (e.g., overall oscillatory and reward system activity related to musical pleasure processing, measured on frontotemporal sites in the theta-frequency band). 55,56 We also expected higher physiological coupling when people reported similar degrees of emotions. In terms of the influence of the social context, we hypothesized that the closer the participants were physically, the higher the coupling would be.…”
Section: Introductionmentioning
confidence: 77%
“…We do not suggest that listener engagement ceases or decreases at the musical climax, but rather that the specific nature of engagement at this point is not evident or indexed by ISC. Recent work by Chabin et al (2020) has used EEG oscillatory band power to identify neural correlates of chills and emotional pleasure during natural music listening, while Czepiel et al (2020) linked ISC of physiological responses to live music to musical elements such as structural segmentation boundaries. Thus, future work could consider using EEG-ISC alongside complementary analysis approaches and response modalities to more fully characterize listener experiences of music.…”
Section: Discussionmentioning
confidence: 99%